Uniqueness of global weak solution for some hyperbolic conservation system (2014)
Abstract. In the present work, we study the uniqueness of entropy solutions for the Riemann and Cauchy problems associated to the Suliciu relaxation system where the initial data satisfies the conditions H1 and H2. Moreover, the solution is in L∞ space. Also, we show the explixit solutions for the Cauchy problem and generalized Riemann problem. When the condition H1 is not satisfied delta shock solutions are obtained for the Riemann problem associated to the Suliciu relaxation system. To guarantee uniqueness of delta shock solutions, we employ a generalization of the Rankine-Hugoniot condition together with a suitable entropy condition.